Tax shields in Colombia and their effect on leverage and investments (2014)
Investment tax incentives may reduce firm leverage if there is indeed an optimal leverage. To test this hypothesis this article assembles a panel database of non-listed Colombian firms from 1995 to 2012, to study the determinants of leverage and investment and the effect of 863 Act of 2003 (An investment tax incentive law) on this firm policy. The results support the hypothesis of a reduction of financial leverage, and the existence of an optimum level of financial leverage, with the advent of the 863 Act, but are less conclusive with respect to an increase in the investment levels. The effect of explanatory variables of financial leverage, according to the theories of financial structure, is unequivocally reduced, as expected, during the life of 863 Act.